Preparation and effectiveness evaluation of DNA methylation photoelectrochemical sensor based on 3-D rigid DNA bridge nanoprobes - ZHU Chuiyu (Di-san junyi daxue xuebao, 2022)
Objective To construct a photoelectrochemical (PEC) sensor based on a 3-dimensional (3-D) rigid DNA bridge nanoprobe for the analysis of DNA methylation sites. Methods Titanium dioxide (TiO2) suspension was dropped onto the surface of ITO electrode to form a thin film; gold nanoparticles (AuNPs) were deposited on the TiO2 nanofilm by potentiometric stripping, and then the 3-D rigid DNA bridge probe was fixed to the electrode surface by Au-S binding. Furthermore, the 5-methylcytosine antibody and cadmium telluride quantum dots (Ab-CdTe QDs) conjugate were prepared. In the presence of the target sequence, the 5-methylcytosine specifically bound to the antibody, and made Ab-CdTe QDs connect to the electrode surface, and then a co-sensitized structure with AuNPs/TiO2 was formed to enhance the photoelectric signal. The PEC signal response of the sensor was measured in phosphate buffer (PBS) containing L-ascorbic acid (AA). Results 3-D rigid DNA bridge nanoprobes were successfully prepared. The optimal concentration of TiO2 suspension was 4 mg/mL, and that of 5-methylcytosine antibody was 10 μg/ml. Under the optimal experimental conditions, 5 electrodes prepared under the same condition were tested parallelly, and the relative standard deviation (RSD) was only 1.8%. After 4 weeks, the photocurrent of the sensor still maintained 92.5% of the initial value. Meanwhile, the sensor presented good selectivity to the target sequence, and the photoelectric response value exhibited a linear relationship with the number of DNA methylation sites. The regression equation was ΔI=-0.004 7+4.011 4×N, and the coefficient of determination R2 was 0.999 7. Conclusion The developed photoelectrochemical sensor involves excellent stability and specificity, and can be used for quantitative detection of multi-site DNA methylation.